Qualitative and Quantitative Data on the Use of the Internet for Archaeological Information. (23rd April 2015) - Richardson, Lorna-Jane
These survey results are from an online survey of 577 UK-based archaeological volunteers, professional archaeologists and archaeological organisations. These data cover a variety of topics related to how and why people access the Internet for information about archaeology, including demographic information, activity relating to accessing information on archaeological topics, archaeological sharing and networking and the use of mobile phone apps and QR codes for public engagement. There is wide scope for further qualitative and quantitative analysis of these data.